Individual Depictions, Causes, and Consequences: Effects of Media Frames on Perceptions Toward the Rural Opioid Epidemic - Cara Lawson; Courtney Meyers; Amber McCord; Erica Irlbeck; Amy Boren (Journal of Applied Communications, 2021)
Rural America faces challenges unique from other parts of the United States with vulnerabilities leaving its potential resilience at risk. In particular, issues associated with public health leave many in rural communities in lack of needed care and resources to maintain a healthy lifestyle. The rural opioid epidemic has added greater challenges to an already fragile rural health system. The mass media has for many decades served as a vessel for health promotion and health campaigns have been successful at changing levels of knowledge. Given that acceptance or action on an issue can be a result of how the message is framed, the purpose of this study was to determine the effects of media frames on attitudes toward the rural opioid epidemic. A framing treatment featuring a story of person in recovery significantly affected perceptions of stigma beliefs. However, while previous studies found describing certain causes associated with addiction to be effective in changing stigma perceptions, that was not the case in this study which suggested not all causal frames are created equally. Additionally, while participants expressed a variety of blame perceptions for the rural opioid epidemic, there were no significant differences based upon the frame that was presented. Finally, policy support was not influenced by participant community types, but there were significant differences in support based upon political party affiliation indicating the rural opioid epidemic represents another example of a social issue with political influence.
Keywords: framing; rural opioid; rural health